Pooling vs. Purchase: The Effects of Accounting for Mergers on Stock Prices. - Hong, Hai; Kaplan, Robert S.; Mandelker, Gershon (The Accounting Review, 1978)
Whether the method of accounting for mergers affects the stock prices of the acquiring firm is investigated in this article. Many observers believe that companies using the pooling-of-interests method in an acquisition with positive goodwill enjoy higher stock prices because of the higher earnings they report when using this method. An efficient capital market, however, should be able to see through the particular accounting convention used to describe an event, such as a merger, and respond to the economics of the merger, not its accounting description The study analyzes a sample of pooling-of-interests mergers in the 1954-1964 period, and finds no abnormal price movements in the period surrounding the merger or the earnings announcements immediately after the merger. Conversely, some evidence of higher stock prices in the period preceding a merger for a much smaller sample of companies using the purchase method is found. The authors conclude that the pooling-of-interests method does not lead to abnormal stock price behavior for acquiring firms.